БАСЛАЎЫШ КЛАССТА МАТЕМАТИКА САБАҚЛАРЫН ОҚЫТЫЎДЫҢ СЫПАТЫН ҲӘМ НӘТИЙЖЕЛИЛИГИН АСЫРЫЎ ЖОЛЛАРЫ - Ихласов, У.; Ихласов, И. (SCIENCE and SOCIETY, 2018)
The article deals with the problems of further improving of teaching mathematics in elementary classes of secondary schools. The author suggests some practical methods- mathematical games which are often used in stages from the very beginning. The model of mathematical tasks are simple and they correspond to children's ages.
Keywords: game activity; studying (learning) activities; game exercises; oral calculation; picking figures; didactic models; solution of mathematical tasks; uninterrupted mathematical education; abstract logical mind; mathematical tables; calculations